ANALISIS PEMBERIAN KOMPENSASI SELAMA BEKERJA DARI RUMAH (WFH) DIMASA PANDEMI PADA CV. SYIFANI ASSA MANDIRI - Dedi Rianto Rahadi; Afrida Nuzul Syifani (The Asia Pacific Journal Of Management Studies, 2021)
In running the company and other work businesses, the role of employees is one of the most important roles in the success of the company (office). Human resources are likened to a company valuable asset because they are also another form of investment for the company itself. Employee performance is also related to the success of the company, so what is the reference for being able to maximize employee performance? Apart from a good environment, salary and responsibility arrangements also affect employee performance. This journal is written qualitatively using observation data collection methods, interviews and documentation through journals, books and related discussions. The results of this study indicate that there is no reduction in compensation or wages during employee WFH but the value remains meaningful for employees considering the needs of the various pandemics.